PENERAPAN METODE ASOSIASI DATA MINING PADA E-COMMERCE TOKO NADHIRA - Inda Anggraini (STMIK KAPUTAMA, 2023)
The purpose of this problem is to produce e-commerce using the association data mining method with the FP-growth algorithm to determine the products that appear most frequently. It also aims to make it easier for buyers and visitors to find products that are most frequently accessed by visitors. At the Nadhira Batik shop, the sales process is conventional, namely visitors come directly to the store and sort the clothing products to be purchased for the payment process, which is also done directly to the cashier. The media used for sales are also still limited, especially for payments that cannot be made through the system. The method used is the association method with the FP-Growth algorithm while the system development method used is waterfall development with the stages of analysis, design, coding, testing and implementation. The results of this study are e-commerce using the FP-Growth data mining association algorithm to determine the products that appear most frequently.